REVIEW LITERATUR KEEFEKTIFAN MOBILISASI DINI PADA POST OPERASI PERBAIKAN TENDON FLEKSOR - Sapto Haryatmo (Jurnal Kesehatan, 2021)
Objectives: The objective of this literature review is to find evidence that exist for the effects of early mobilisation of post flexor tendon repair surgery in order to inform the professional practitioners of its benefit or otherwise. Methods: This literature review was conducted by electronic searching of journal databases using the specified keywords. Result: Early mobilisation of post flexor tendon repair surgery showed a better result in the function recovery, faster healing process, prevent contracture and minimal complication of flexor tendon. It is also give a better healing than total immobilisation. Early mobilisation of the flexor tendon which is done by well trained personnel and under controlled on comply to the order patient could avoid the complication to the repaired tendon. Both passive and active early mobilisation have no significance defference in bad effect or complication to the tendon. Conclusion: Early mobilisation both passive or active on post flexor tendon repair surgery give positive effect in restore tendon function. The minimal effect and complication is very helpful to the service and money spending of the patients.